Theoretical analysis and design for a multilayered ionic polymer metal composite actuator. (February 2018) - Yang, Woosung; Choi, Sooho; Kim, Hyungjoo; Cho, Whang; Lee, Sungon
Ionic polymer metal composites with a flexible large deformation have been used as biomimetic actuators and sensors in various fields. This work mainly focuses on the validation of the proposed theoretical prediction for various ionic polymer metal composite applications, such as a field needing a large resultant force, large tip deflection, or high response frequency. Such properties can be controlled by the number of layers and the thickness ratio of a multilayered ionic polymer metal composite actuator. Thus, we considered major design factors such as the number of layers and the thickness ratio in analysis of the proposed theoretical model and performed experiments to verify the static and dynamic electromechanical responses of multilayered (multimorph) ionic polymer metal composite structures acting as actuators. The relation between the polymer (Nafion) and electrode or substrate is represented by β . From this theoretical analysis, three properties were analyzed and predicted based on the Euler–Bernoulli beam theory, considering the dynamics of the ionic polymer metal composite, electrode, and bonding layers (substrate layers). The predicted results of a symmetric ionic polymer metal composite multimorph were compared with results of finite element analysis and experiments using ionic polymer metal composite multimorphs with one to five layers. Finally, this work examined how the number of layers and thickness affect the dynamic properties. This can contribute to predicting and optimally designing a multilayered ionic polymer metal composite actuator for satisfying a specific requirement.